(untitled) (Web of Teachers: Inderscience Research, 2026)
This article is devoted to identifying strategies for using specific features in teaching English, as well as studying methods for demonstrating the professional and psychological potential of veterinary students through English. The article examines issues related to the use of pedagogical technologies in teaching English to veterinary students in the modern educational process, emphasizing that the effectiveness of lessons largely depends on the teacher’s ability to engage students and motivate them to learn.